Examining hemodialyzer membrane performance using proteomic technologies - Bonomini M; Pieroni L; Di Liberato L; Sirolli V; Urbani A (Dove Medical Press, 2017)
Mario Bonomini,1 Luisa Pieroni,2 Lorenzo Di Liberato,1 Vittorio Sirolli,1 Andrea Urbani2,3 1Department of Medicine, G. d’Annunzio University, Chieti, 2Proteomic and Metabonomic Units, IRCCS S. Lucia Foundation, Rome, 3Faculty of Medicine, Biochemistry and Clinical Biochemistry Institute, Catholic University of the “Sacred Heart”, Rome, Italy Abstract: The success and the quality of hemodialysis therapy are mainly related to both clearance and biocompatibility properties of the artificial membrane packed in the hemodialyzer. Performance of a membrane is strongly influenced by its interaction with the plasma protein repertoire during the extracorporeal procedure. Recognition that a number of medium–high molecular weight solutes, including proteins and protein-bound molecules, are potentially toxic has prompted the development of more permeable membranes. Such membrane engineering, however, may cause loss of vital proteins, with membrane removal being nonspecific. In addition, plasma proteins can be adsorbed onto the membrane surface upon blood contact during dialysis. Adsorption can contribute to the removal of toxic compounds and governs the biocompatibility of a membrane, since surface-adsorbed proteins may trigger a variety of biologic blood pathways with pathophysiologic consequences. Over the last years, use of proteomic approaches has allowed polypeptide spectrum involved in the process of hemodialysis, a key issue previously hampered by lack of suitable technology, to be assessed in an unbiased manner and in its full complexity. Proteomics has been successfully applied to identify and quantify proteins in complex mixtures such as dialysis outflow fluid and fluid desorbed from dialysis membrane containing adsorbed proteins. The identified proteins can also be characterized by their involvement in metabolic and signaling pathways, molecular networks, and biologic processes through application of bioinformatics tools. Proteomics may thus provide an actual functional definition as to the effect of a membrane material on plasma proteins during hemodialysis. Here, we review the results of proteomic studies on the performance of hemodialysis membranes, as evaluated in terms of solute removal efficiency and blood–membrane interactions. The evidence collected indicates that the information provided by proteomic investigations yields improved molecular and functional knowledge and may lead to the development of more efficient membranes for the potential benefit of the patient. Keywords: mass spectrometry, hemodialysis, end-stage renal disease, protein adsorption, biocompatibility, uremic toxin